2001
DOI: 10.1161/01.cir.103.21.e101
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trials in Cardiovascular Medicine

Abstract: he practice of cardiology is increasingly driven by evidence-based medicine centering around the results of clinical trials. 1 In this inaugural article of Clinical Cardiology: Physician Update, I will focus on the design, analysis, and interpretation of clinical trials in cardiovascular medicine. Armed with the tools described herein, clinicians will be better equipped to understand and synthesize the results of the multitude of clinical trials appearing in the cardiology literature. A major goal of this effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…By doing so, a type II error (i.e., erroneous declaring that there is actually a difference between two treatments) might be possible. 26 However, the mean difference between the patients randomized to azithromycin and those to placebo was À7.58 hr (95% CI À33.5 to 18.3 hr). As this difference is well between the pre-specified range of assumed equivalence, our study was adequately powered and its results statistically valid despite the lower inclusion rate.…”
Section: Discussionmentioning
confidence: 95%
“…By doing so, a type II error (i.e., erroneous declaring that there is actually a difference between two treatments) might be possible. 26 However, the mean difference between the patients randomized to azithromycin and those to placebo was À7.58 hr (95% CI À33.5 to 18.3 hr). As this difference is well between the pre-specified range of assumed equivalence, our study was adequately powered and its results statistically valid despite the lower inclusion rate.…”
Section: Discussionmentioning
confidence: 95%
“…26 As a result, increasing numbers of patients are needed to show a difference between treatment groups because the net number of clinical events, rather than the number of patients enrolled in a trial, ultimately determines a trial’s overall power to detect a significant difference. 26,27 Historically, the development of the composite endpoint was one of the first ways trial design was adapted to leverage this knowledge. 28 Further innovations in the design and implementation of clinical trials, including targeted patient recruitment, can increase the efficiency of heart failure trials.…”
Section: Discussionmentioning
confidence: 99%
“…The alternative hypothesis above implies that at least I − k trials have shown the noninferiority, to which we refer as "consistency of noninferiority." This hypothesis setting has been used by many authors (see e.g., Antman, 2001;Garcia, 2005;Pater, 2004) in practical noninferiority trials. The integer k is a threshold representing the number of "inferior" trials that could be tolerated among I trials, while the consistency of noninferiority among all trials is still confirmed.…”
Section: The Testing Procedures Based On Multiple Meansmentioning
confidence: 99%